2004
DOI: 10.1249/01.mss.0000132378.73975.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ingestion of Bicarbonate, Citrate, Lactate, and Chloride on Sprint Running

Abstract: Bicarbonate is possibly more beneficial to sprint performance than lactate and probably more beneficial than citrate or chloride. We recommend ingestion of sodium bicarbonate to enhance sprint performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
2
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 19 publications
10
71
2
10
Order By: Relevance
“…Although these effects on performance might appear small, they are of considerable significance to the athlete, for whom an improvement of even a fraction of a second in these events is considered to be a major achievement. In a study by VanMontfoort et al [10], ingestion of sodium bicarbonate was found to increase the sprint performance in elite male athletes compared to citrate, lactate and chloride ingestion.…”
Section: Evidences For Improvement In Performancementioning
confidence: 94%
See 1 more Smart Citation
“…Although these effects on performance might appear small, they are of considerable significance to the athlete, for whom an improvement of even a fraction of a second in these events is considered to be a major achievement. In a study by VanMontfoort et al [10], ingestion of sodium bicarbonate was found to increase the sprint performance in elite male athletes compared to citrate, lactate and chloride ingestion.…”
Section: Evidences For Improvement In Performancementioning
confidence: 94%
“…This in turn could delay the onset of fatigue [8]. Studies [9,10] have confirmed that increased extracellular pH and higher bicarbonate raise the H + and lactic acid efflux from active muscles. This is due to an increase in the activity of the Lactic acid/H + co-transporter, which becomes more active as the intracellular/extracellular H + gradient increases, during contraction as well as during recovery.…”
Section: Acting Mechanismmentioning
confidence: 97%
“…Por outro lado, Slaler et al 55 não encontraram mudança na força nem na composição corporal de atletas, adultos jovens, sob treino de resistência após a suplementação oral de betahidroximetilbutirato na dose deum aumento no pH plasmático, o qual leva a um atraso no início da acidificação intracelular durante o exercício. Van Montfoort et al 57 , num estudo duplo-cego randomizado com 15 corredores, concluíram que o bicarbonato é mais benéfico em aumentar o desempenho do que placebo ou outros agentes tampões.…”
Section: Betahidroximetilbutiratounclassified
“…These decrements in performance can also be related to the accumulation of metabolites during exercise such as hydrogen ions resulting from increased lactic acid formation in high intensity exercise (44). Creatine monohydrate, and sodium bicarbonate, are two widely-studied ergogenic aids that have shown to attenuate the decline in fatigue while also increasing power output in high intensity exercise bouts such as sprinting (1,3,4,7,8,11,12,16,31,32,55,65,68).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Current research has shown that ingesting sodium bicarbonate may enhance aspects of sprint performance such as power output, total anaerobic work, and delaying fatigue (7,8,32,38,39,40,41,42,65). Lavender and Bird (1989), and Bishop et al (2004Bishop et al ( -2005, concluded that sodium bicarbonate supplementation improved power output levels in repeated sprints.…”
Section: Statement Of the Problemmentioning
confidence: 99%